The Consequences of Disobeying the Patriarchal Values in Niki Caro’s North Country and Steven Soderbergh’s Erin Brockovich - Jessica Puspa; Priska Febrinia Handojo (Institute of Research and Community Outreach - Petra Christian University, 2013)
This study aims to understand the consequences that Josey Aimes and Erin Brockovich face in disobeying the patriarchal values in North Country and Erin Brockovich. Patriarchal society where Aimes and Brockovich live, demands that the roles of women are as domestic creatures. If they cannot accept their roles, as the consequences, they will be punished by the people who guard the patriarchal values. It can be seen that Aimes and Brockovich are still bound by the patriarchal values which inhibit their position to express themselves. Their effort to get equality shows how the patriarchal values are deeply rooted in their society because both men and women guard those values.